(untitled) - Mader, Sylvia S.; Sylvia S. Mader (Dubuque, IA, 2008)
The Laboratory Manual to accompany Sylvia Mader's Human Biology reflects all of the exceptional features of the Human Biology text. Instructors appreciate the refined exercises that are so numerous you won't need to look anywhere else for student activities. Author Sylvia Mader's writing in the laboratory manual, just as in the text, emphasizes clarity, with carefully worded study questions that are direct in their intent and purpose
Keywords: Human biology